Ponder: contemplative Bible study year C - Leonard-Fleckman, Mahri (Collegeville, Minnesota: Liturgical Press, 2021)
Ponder: Contemplative Bible Study accompanies all hearers and preachers of the Word as they pray with and ponder the Sunday readings throughout the liturgical year. Everything needed for a rich experience of lectio divina and biblical exploration is provided: the full text of the Sunday readings, concise commentary, engaging reflections, and clear guidance on how to use this resource alone or with a group. This volume guides readers through the Year C lectionary. -- Publisher
Keywords: Church year meditations; Bible -- Meditations; Catholic Church -- Prayers and devotions; Catholic Church. Lectionary for Mass (U.S.)